Developing Arabic Teaching Materials Based on Local Culture to Enhance Reading Skills And Its Implications on Self-Regulated Learning - Bambang Irawan (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2023)
This article outlines the integration of local culture into the development of Arabic language teaching materials, aiming to enhance students' reading skills. The research, categorized as Research and Development, involved class X students and Arabic language teachers at Madrasah Aliyah Nuris in Jember Regency, East Java. The teaching materials underwent five stages: analysis, design, development, implementation, and evaluation, including the validation of assessment instruments and analysis of validation data. Research findings on the development of teaching materials grounded in local cultural content unfolded through distinct phases. These included the design of teaching material products, systematically organizing the primary study materials; the presentation of trial results for Arabic language teaching materials infused with local culture, featuring regional song culture and images of the surrounding environment to engage student interest; and the analysis of expert assessments and student responses to these teaching material products. The unique impact of Local Culture-Based Arabic language teaching materials on self-regulation was evident in students' adeptness at overcoming learning challenges, practicing self-regulation and enhanced focus, aiding comprehensive understanding of various ideas and subjects. This proficiency enabled them to apply their knowledge in practical scenarios and fostered creativity in overcoming hurdles in learning to read Arabic texts.